2014
DOI: 10.17352/2455-8583.000004
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Risk Estimation according to the Framingham-Wilson Score and Impaired Fasting Glucose in Adult Subjects from Maracaibo city, Venezuela

Abstract: Introduction: Type 2 Diabetes Mellitus (T2DM) is an independent risk factor for coronary artery disease. Nevertheless, the coronary risk rendered by pre-diabetes states such as Impaired Fasting Glucose (IFG) has not been thoroughly explored. The purpose of this study was to evaluate the influence of glycemic status on coronary risk estimated by the recalibrated Framingham-Wilson equation in our population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 53 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Various studies have been conducted to assess the impact of sex on diabetes-associated CV risk. 24 - 26 In a cohort of 1,378 subjects selected from the Maracaibo City Metabolic Syndrome Prevalence Study, significantly higher coronary risk was observed in men with normoglycemia (3.28%) than women with normoglycemia (2.05%) ( P <0.001) and in men with IFG (4.90%) than women with IFG (2.75%) ( P <0.001). Although the overall risk was greater in subjects with diabetes than in subjects with normoglycemia or IFG, no sex differences were evident.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have been conducted to assess the impact of sex on diabetes-associated CV risk. 24 - 26 In a cohort of 1,378 subjects selected from the Maracaibo City Metabolic Syndrome Prevalence Study, significantly higher coronary risk was observed in men with normoglycemia (3.28%) than women with normoglycemia (2.05%) ( P <0.001) and in men with IFG (4.90%) than women with IFG (2.75%) ( P <0.001). Although the overall risk was greater in subjects with diabetes than in subjects with normoglycemia or IFG, no sex differences were evident.…”
Section: Discussionmentioning
confidence: 99%
“…Although the overall risk was greater in subjects with diabetes than in subjects with normoglycemia or IFG, no sex differences were evident. 24 A meta analysis of 37 prospective cohort studies of T2DM and fatal CHD among 447,064 subjects revealed that the relative risk for fatal CHD associated with diabetes was 50% greater in women than in men. 26 However, in the present study, the FRS in men was higher than that in women in both pre-diabetes and diabetes groups, indicating a clear sex difference.…”
Section: Discussionmentioning
confidence: 99%